Management of Differentiated Instruction in Improving Mathematics Learning Outcomes for Fifth Grade in Elementary School - Nurhayati Nurhayati; Teti Ratnawulan Surtiati (Journal of Science and Education (JSE), 2026)
Mathematics learning in elementary schools often faces challenges due to differences in students' readiness, interests, and learning styles. To address these issues, the systematic implementation of differentiated instruction management is necessary. This study aims to describe the implementation of differentiated instruction management in improving the mathematics learning outcomes of fifth-grade elementary school students, based on George R. Terry's management theory, which includes the functions of planning, organizing, actuating, and controlling. The research uses a qualitative approach with a case study design conducted at SDN Sukamanah and SDN Samudralaksana, Cianjur Regency, with data collected through observation, in-depth interviews, and document analysis, and then analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The results show that in the planning stage, teachers design learning strategies that consider student diversity; in the organizing stage, teachers prepare media, resources, and methods to support the differentiation of content, process, and product; in the actuating stage, teachers implement collaborative and responsive learning that addresses individual needs; while in the controlling stage, formative and summative evaluations, teacher reflection, and follow-up improvements are carried out. Thus, this study concludes that the application of differentiated instruction management based on Terry's theory can increase student engagement, accommodate learning differences, and positively impact the mathematics learning outcomes of fifth-grade elementary school students.